2019
DOI: 10.1186/s12877-019-1109-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between superoxide dismutase, malondialdehyde and all-cause mortality in older adults: a community-based cohort study

Abstract: Background Oxidative stress is an important theory of aging but population-based evidence has been lacking. This study aimed to evaluate the associations between biomarkers of oxidative stress, including plasma superoxide dismutase (SOD) activity and malondialdehyde (MDA), with all-cause mortality in older adults. Methods This is a community-based cohort study of 2224 participants (women:1227, median age: 86 years). We included individuals aged 65 or above and with plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…In the present study, low baseline serum levels of TAS, SOD, and high MDA could accelerate the progression of PACG. Limited data are available in the literature regarding the association of oxidative stress markers with PACG progression, but there has been increasing evidence showing that TAS, SOD, and MDA levels could serve as biomarkers to predict the progression or survival of different types of other diseases [ 33 36 ]. For example, Chen et al [ 33 ] performed a community-based cohort study of 2224 participants reporting that increased activity of SOD was independently associated with lower all-cause mortality in older women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, low baseline serum levels of TAS, SOD, and high MDA could accelerate the progression of PACG. Limited data are available in the literature regarding the association of oxidative stress markers with PACG progression, but there has been increasing evidence showing that TAS, SOD, and MDA levels could serve as biomarkers to predict the progression or survival of different types of other diseases [ 33 36 ]. For example, Chen et al [ 33 ] performed a community-based cohort study of 2224 participants reporting that increased activity of SOD was independently associated with lower all-cause mortality in older women.…”
Section: Discussionmentioning
confidence: 99%
“…Limited data are available in the literature regarding the association of oxidative stress markers with PACG progression, but there has been increasing evidence showing that TAS, SOD, and MDA levels could serve as biomarkers to predict the progression or survival of different types of other diseases [ 33 36 ]. For example, Chen et al [ 33 ] performed a community-based cohort study of 2224 participants reporting that increased activity of SOD was independently associated with lower all-cause mortality in older women. A meta-analysis of five prospective studies showed that a significant inverse association was found between dietary TAS and all-cause mortality (combined effect size = 0.62, 95%CI = 0.60–0.64), cancer (combined effect size = 0.81, 95%CI = 0.75–0.88), and cardiovascular disease mortality (combined effect size = 0.71, 95%CI = 0.63–0.82) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it has been recently demonstrated that SOD activity is higher in women than in men [81], which could help explain why men tend to be more common victims of Winiwarter-Buerger disease [4,47,66].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant enzymes, such as glutathione peroxidase (GPx), superoxide dismutase (SOD), and catalase (CAT), serve as a primary defense system against oxidative stress [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Although these scavenger enzymes at first are inactivated when counteracting ROS, their expression is induced by the presence of reactive species [ 41 ].…”
Section: Discussionmentioning
confidence: 99%